Advanced diamond-reinforced metal matrix composites via cold spray: properties and deposition mechanism - Yin, Shuo; Xie, Yingchun; Cizek, Jan; Ekoi, Emmanuel; Hussain, Tanvir; Dowling, Denis; Lupoi, Rocco (Elsevier, 2017)
Diamond-reinforced metal matrix composites (DMMC) have great potential for wear-resistance applications due to the superior hardness of the diamond component. Cold spray as an emerging coating technique is able to fabricate coatings or bulk materials without exceeding the material melting point, thereby significantly lowering the risk of oxidation, phase transformation, and excessive thermal residual stress. In this paper, thick DMMC coatings were deposited onto aluminum alloy substrate via cold spray of three feedstock powders: copper-clad diamond and pure copper, and their mixtures. It was found that, due to its low processing temperature, cold spray is able to prevent graphitization of the diamond in the DMMC coatings. Further to that, the original diamond phase was almost completely retained in the DMMC coatings. In case of the coatings fabricated from copper-clad diamond powders only, its mass fraction reached 43 wt.%, i.e. value higher than in any previous studies using conventional pre-mixed powders. Furthermore, it was found that the added copper content powders acted as a buffer, effectively preventing the fracture of the diamond particles in the coating. Finally, the wear test on the coatings showed that the cold sprayed DMMC coatings had excellent wear-resistance properties due to the diamond reinforcement.